Academic Advising and Career Services: A Collaborative Approach. Issue 148 (December 2014) - Ledwith, Katherine E.
Abstract : This chapter describes how career services professionals and academic advising units can partner to serve college students. Observations are also provided regarding the role of advising and best practices to meet the growing need for a shared approach to the academic and career needs of students.